Population knowledge and awareness of antibiotic use and antimicrobial resistance: results from national household survey 2019 and changes from 2017 - Viroj Tangcharoensathien; Sunicha Chanvatik; Hathairat Kosiyaporn; Supapat Kirivan; Wanwisa Kaewkhankhaeng; Apichart Thunyahan; Angkana Lekagul (BMC, 2021)
Abstract Background Lack of knowledge and awareness on antimicrobial resistance (AMR) can result in irrational use of antibiotics, which is one of the major drivers of AMR. One goal of the Thailand National Strategic Plan on AMR (2017-2021) is a 20% increase in public knowledge and awareness of antibiotic use and AMR by 2021. This study assesses antibiotic use, level of knowledge and awareness of antibiotic use and AMR and the factors associated with their knowledge and awareness in the Thai population in 2019. It compares findings with a similar national survey in 2017. Methods An AMR module was integrated into the Health and Welfare Survey, a biennial national household survey conducted by the National Statistical Office since 2017. The 2019 survey took place in March, through face-to-face interviews with 27,900 Thai adults aged 15 years or above who participated in the survey and compares 2019 findings with those from 2017. Results One month prior to the survey, 6.3% of population reported use of antibiotics (reduced from 7.9% to 2017), of which 98.1% received antibiotics through healthcare professionals and almost half (43.2%) for flu symptoms. During the last 12 months, 21.5% of Thai adults received information on the appropriate use of antibiotics and AMR (increased from 17.8% to 2017); mostly through health professionals (82.7%). On knowledge, 24.3% of adults gave correct answers to more than three out of six statements (three true and three false statements) (increased from 23.7% to 2017). The overall mean score of awareness of appropriate antibiotic use and AMR is 3.3 out of total score of 5. Conclusions Although progress was made on knowledge and awareness between 2017 and 2019, certain practices, such as use of antibiotics for flu symptoms and receiving information about antibiotic use and AMR, are inappropriate and inadequate. These findings require significant action, notably strengthening health professionals' ability to prescribe and dispense antibiotics appropriately and effective communication with patients. The government should promote specific information on rational use of antibiotics and AMR to specific target groups.